The Implication Of Teacher Professionalism Improvement And Learning Evaluation Techniques Toward Madrasah Teacher Performance - Aqil, Deden Ibnu; Setiawati, Nur Amega; Kurniadi, Fajar (Tarbiyah : Jurnal Ilmiah Kependidikan, 2020)
The ability of a teacher to understand his or her competence greatly determines the success of his students, because students will develop if the teachers are able to develop themselves by increasing their professionalism. This research method used a quantitative approach with a sample of teachers at Madrasah Ibtidaiyah Miftahul Falah Depok. The results of this study indicate that there is no positive and significant influence both activities to increase teacher professionalism and learning evaluation techniques on teacher performance at the Mifathul Falah Sawangan school, Depok.